Pemberdayaan Guru Cerdas Finansial Melalui Teknologi Informasi dalam Upaya Meningkatkan Portofolio Keuangan Keluarga di SMKN 26 Rawamangun Jakarta Timur - Murdayanti, Yunika; Hasanah, Nuramalia; Muliasari, Indah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
A good pattern of financial management will be very helpful in meeting the needs of life now and in the future. Financial intelligence is important for everyone. Therefore sufficient knowledge is needed. By understanding all existing financial and investment products, and mastering financial mathematics, someone can improve their financial intelligence. This method of community development is carried out at Vocational School 26 to improve financial literacy in generating computerized family financial reports. These activities consist of 1) understanding of financial literacy, 2) recording of a good family financial portfolio, 3) providing facilities and infrastructure through the procurement of equipment and practical materials, 4) mentoring in the form of consultation and guidance in making financial reports through information technology namely family financial applications. Conclusion of this community development activity is the participants have been able to increase knowledge about family financial management and the feedback given by the participants to the interest in the speaker and the material presented also positive enthusiasm by participating in discussion session.